Compression of bitcoin blockchain - Xiaojiao CHEN; Xianzheng LIN; Nenghai YU (网络与信息安全学报)
The blockchain provides an immutable, transparent, and decentralized method for data storage.However, as the volume of data gradually increases, the public blockchain system requires significant storage space.The bitcoin block's structure was analyzed.A method was introduced to compress the size of transactions in the bitcoin blockchain by encoding specific fields.Experiment shows that the proposed method can reduce the storage space of the bitcoin blockchain by 18.13%.